Sunflower oil hydrogenation on Pd/Al2O3 catalysts in single-phase conditions using supercritical propane - Piqueras, Cristian Martin (2006)
Several Pd catalysts were prepared on α and γ alumina using palladium acetylacetonate and palladium nitrate as a precursor. The characterization of these catalysts by H2 chemisorption, XRD and TEM microscopy confirm the presence of different dispersed metallic particles from 1.9 to 12.1 nm. These catalysts were tested in the sunflower oil hydrogenation under supercritical conditions using propane as solvent and 5% mol of hydrogen concentration. The well-known Weisz-Prater criterion was used to determine the extent of mass transport phenomena. While hydrogen mass transport was found free from limitations, oil transport had limitations in some experiments. The reaction is moderately structure sensitive since the turnover number decreases 3 times as the exposed metal percentage (metal dispersion) increases from 9 to 60%. An influence on the selectivities to trans isomers, monounsaturated and saturated fatty acids was found when the metallic particle size was decreased. These results are explained by the high adsorption strength of the high-unsaturated fatty acids onto the small particles and the promotion of a "shunt" reaction from linoleic to saturated compounds. © 2006 Elsevier B.V. All rights reserved.